When more means less: the declining happiness premium of higher education in wealthier countries - Samitha Udayanga (Humanities & Social Sciences Communications)
Abstract The association between education and subjective well-being is well established, particularly in terms of educational-level coefficients estimated in standard subjective well-being models. The present study aligns with these findings and further contributes to understanding gender differences in the benefits derived from higher education, and how these are influenced by country-level social and economic development. The analysis is based on data from the European Social Survey (which included 36 countries). Applying multi-level modeling techniques, the study finds that both less educated and highly educated individuals experience a steady increase in well-being as a country’s social and economic prosperity gradually improves, with highly educated individuals enjoying greater advantages up to a certain point (even without any significant gender difference). However, when a country’s social and economic conditions become particularly strong, the well-being gains associated with higher education tend to level off. This does not imply that they are unhappy; instead, it suggests that relative to less educated individuals, highly educated people experience slightly lower levels of happiness. Therefore, in more affluent countries, less educated individuals are comparatively advantaged in terms of happiness, as their happiness drivers may still be associated with conventional life circumstances (such as income). Overall, these findings imply that in wealthier countries, the happiness derived from higher education tends to weaken, suggesting that highly educated individuals are more likely to pursue alternative avenues for happiness, moving away from the conventional drivers identified in previous happiness studies.